Impact of suboptimal donor to suboptimal recipient kidney transplant on delayed graft function and outcome - Bocchi, Federica; Beldi, Guido; Kuhn, Christian; Storni, Federico; Müller, Natalie; Sidler, Daniel (Frontiers in Transplantation, 2023)
The demographics of donor and recipient candidates for kidney transplantation (KT) have substantially changed. Recipients tend to be older and polymorbid and KT to suboptimal recipients is associated with delayed graft function (DGF), prolonged hospitalization, inferior long-term allograft function, and poorer patient survival. In parallel, donors are also older, suffer from several comorbidities, and donations coming from circulatory death (DCD) predominate, which in turn leads to early and late complications. However, it is unclear how donor and recipient risk factors interact. In this retrospective cohort study, we assess the impact of a KT from suboptimal donors to suboptimal recipients. We focused on: 1) DGF; 2) hospital stay and number of dialysis days after KT and 3) allograft function at 12 months. Among the 369 KT included, the overall DGF rate was 25% (n = 92) and median time from reperfusion to DGF resolution was 7.8 days (IQR: 3.0-13.8 days). Overall, patients received four dialysis sessions (IQR: 2-8). The combination of pre-KT anuria (< 200 ml/24h, 32%) and DCD procurement (14%) was significantly associated with DGF, length of hospital stay, and severe perioperative complications, predominantly in recipients 50 years and older.